2011
DOI: 10.1210/jc.2011-1003
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length in Neoplastic and Nonneoplastic Tissues of Patients with Familial and Sporadic Papillary Thyroid Cancer

Abstract: Our results demonstrate that short telomeres are a consistent feature of PTC, which in familial cases, is not restricted to the tumor tissue. This finding suggests that FPTC has a distinct, heritable, genetic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 17 publications
5
33
0
Order By: Relevance
“…No mutations were detected in medullary thyroid carcinomas, as described by Killela et al 3 , nor in normal thyroid and benign lesions, such as goitre, adenomas or thyroiditis; this finding fits with previous studies that reported telomerase expression in malignant lesions and not in normal tissue or hyperplastic lesions 8,9 . TERT mutations were associated with clinicopathological features (older age, increased tumour size and a b male gender), but, after histotype stratification, these associations were only maintained in cPTC.…”
Section: Resultssupporting
confidence: 91%
“…No mutations were detected in medullary thyroid carcinomas, as described by Killela et al 3 , nor in normal thyroid and benign lesions, such as goitre, adenomas or thyroiditis; this finding fits with previous studies that reported telomerase expression in malignant lesions and not in normal tissue or hyperplastic lesions 8,9 . TERT mutations were associated with clinicopathological features (older age, increased tumour size and a b male gender), but, after histotype stratification, these associations were only maintained in cPTC.…”
Section: Resultssupporting
confidence: 91%
“…A recent study by Capezzone and colleagues reported telomerase activity in most sporadic and familial malignant thyroid tumours as well as in some adenomas [15]. Telomerase activity was not observed in hyperplastic nodules or in normal thyroid tissue from patients with sporadic PTC [15]. In summary, the aforementioned findings suggest that telomerase activity may be associated with a more aggressive clinical behaviour of thyroid tumours.…”
Section: Telomerase Promoter Mutations In Thyroid Carcinomasmentioning
confidence: 87%
“…A TERT copy number gain was described in familial PTC [14], but this finding was not confirmed in another series [55]. A recent study by Capezzone and colleagues reported telomerase activity in most sporadic and familial malignant thyroid tumours as well as in some adenomas [15]. Telomerase activity was not observed in hyperplastic nodules or in normal thyroid tissue from patients with sporadic PTC [15].…”
Section: Telomerase Promoter Mutations In Thyroid Carcinomasmentioning
confidence: 95%
“…Aneuploidy is a molecular feature that identifies genetic instability, and potentially, higher metastatic capacity, being commonly associated with worse disease prognosis (26,27). In two recent studies of familial PTC, although controversial (28), Capezzone et al observed shorter telomere length in the leukocytes, other non-neoplastic tissues and tumours in the familial cases when compared with patients with sporadic PTC or healthy subjects (29,30). The size reduction of these nucleoprotein complexes, which protect the ends of chromosomes from degradation and fusion, may induce chromosomal instability, and thus, aneuploidy in these familial tumours.…”
Section: Introductionmentioning
confidence: 99%